KOMUNIKASI PUBLIK PEMERINTAH KOTA SUKABUMI DALAM PENGELOLAAN PENGADUAN MASYARAKAT MELALUI APLIKASI SUPER - Ratna Nurseha; Siti Ghaida Sri Afira Ruhyadi (PT Naureen Digital Education, 2023)
The current condition requires every government, both central and regional, to provide quality public services. Service is carried out face to face in the communication process, then develops through mediated communication. One of the efforts to respond to the community's need for a complaint facility, the City Government of Sukabumi launched the Super application (Sukabumi Participatory Responder). In this study, researchers wanted to find out how the public service communication of the Communication and Informatics Office of the City of Sukabumi manages public complaints through the Super application and its flow. This research was conducted with a qualitative approach, which means it will be aimed at examining natural objective conditions. The research was conducted during July-August 2022. located at the Sukabumi City Diskominfo which is located at Jalan R. Syamsudin, SH No. 25, Sukabumi City Hall Complex. Data obtained through literature studies, observations, interviews and documentation. Data analysis techniques namely data reduction, data presentation, drawing conclusions and verification. The validity of the data in this study uses credibility criteria. The Super community application can convey their aspirations on the right channel, maintain the confidentiality of the reporter's identity, and can be followed up by the right party. Diskominfo as the main Adminstrator for application management assigns administrators at each Regional Apparatus Organization to manage complaints at OPD. Furthermore, the admins submit incoming complaint information to the relevant OPD, and are monitored directly by the leadership elements via Whatsapp. Every time a complaint comes to the super application, the administrator verifies the report. Reports that meet the categories will be processed. The various complaints that are often reported include damage to roads, PLN/Telkom cables, PJU and clean water consumers.